Mitochondrial function is impaired in long COVID patients - Jane Macnaughtan; Kai-Yin Chau; Ewen Brennan; Marco Toffoli; Antonella Spinazzola; Toby Hillman; Melissa Heightman; Anthony Henry Vernon Schapira (Annals of Medicine)
Background The Long COVID syndrome is a major global health problem, affecting approximately 10–20% of individuals infected with SARS-CoV-2 virus with many remaining symptomatic beyond one year. Fatigue, reduced exercise tolerance and hyperlactataemia on minimal exertion have led to the suggestion of a bioenergetic defect. We hypothesised that mitochondrial dysfunction is a pathological feature in Long COVID cases and would correlate with clinical outcome.Methods This prospective, case-controlled, observational study recruited 27 participants with an established diagnosis of Long COVID syndrome from a single tertiary clinic together with 16 age-matched controls aged 25–65 years. Seahorse-based mitochondrial flux analysis and bioenergetics profile of isolated peripheral blood mononuclear cells (PBMCs) was performed and correlated with clinical phenotype.Findings Long COVID cases had an increased baseline and ATP-induced oxygen consumption rate with a significant attenuation in tetramethylrhodamine methyl ester perchlorate fluorescence response to oligomycin. Correlations were observed between mitochondrial function and autonomic health, quality of life and time from index infection. Sex-specific differences were also observed.Interpretation PBMCs from Long COVID subjects exhibit an exceptional and distinctive change in ATP synthase, as it contributes to the mitochondrial membrane potential rather than using it exclusively to generate ATP. The findings suggest that the enzyme runs both forward and reverse reactions, synthesising and hydrolysing ATP. The correlation of mitochondrial function with clinical phenotype in Long COVID may indicate a causal relationship and warrants further validation in larger scale studies.